2016
DOI: 10.1634/theoncologist.2015-0336
|View full text |Cite
|
Sign up to set email alerts
|

The PROFILE Feasibility Study: Targeted Screening of Men With a Family History of Prostate Cancer

Abstract: A better assessment of prostate cancer (PrCa) risk is needed to improve screening. The PROFILE pilot study explored the feasibility of single nucleotide polymorphism profiling in men with a family history (FH) of PrCa to investigate the probability of detecting PrCa at prostate biopsy (PB). The results of the present pilot study have demonstrated that PB is a feasible and safe method of PrCa screening in men with a FH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Indeed, calculation of a genetic risk score using the SNPs genotyped in this study allows for the stratification of risk for PCa across a 5‐fold range, ie, men who are in the upper 10% of risk allele carriers are ∼5‐fold more likely to be diagnosed with prostate cancer than men in the lowest 10%. This level of risk is sufficient to warrant consideration of genetic risk estimate calculations for targeted early screening in the general population . The use of SNPs to identify men in the Norwegian population who are at increased inherited risk for PCa and thus would benefit from early disease screening and monitoring could eventually result in significant declines in mortality and morbidity in these men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, calculation of a genetic risk score using the SNPs genotyped in this study allows for the stratification of risk for PCa across a 5‐fold range, ie, men who are in the upper 10% of risk allele carriers are ∼5‐fold more likely to be diagnosed with prostate cancer than men in the lowest 10%. This level of risk is sufficient to warrant consideration of genetic risk estimate calculations for targeted early screening in the general population . The use of SNPs to identify men in the Norwegian population who are at increased inherited risk for PCa and thus would benefit from early disease screening and monitoring could eventually result in significant declines in mortality and morbidity in these men.…”
Section: Discussionmentioning
confidence: 99%
“…This level of risk is sufficient to warrant consideration of genetic risk estimate calculations for targeted early screening in the general population. 19 The use of SNPs to identify men in the Norwegian population who are at increased inherited risk for PCa and thus would benefit from early disease screening and monitoring could eventually result in significant declines in mortality and morbidity in these men.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) over the last decade have identified over 100 germline single nucleotide polymorphisms (SNPs) that show significant association with relevant prostate cancer diagnosis measures, including elevated PSA, family history, and probability of future prostate cancer development [25]. In considering the predictive value of risk SNPs for evaluating men who might benefit from PSA testing, the International Consortium for Prostate Cancer Genetics (ICPCG) evaluated over 12,500 samples and established a significant relationship for 8 risk SNPs and prostate cancer [26].…”
Section: Screen Vs Not Screen: Precision Biomarkers For Risk Assementioning
confidence: 99%
“…Its pilot study, performed in 100 men with a positive family history, demonstrated that screening biopsy is feasible and safe [4]. Research is preliminary; however, results of the ongoing PROFILE study are eagerly awaited.…”
mentioning
confidence: 99%
“…Research is preliminary; however, results of the ongoing PROFILE study are eagerly awaited. Its pilot study, performed in 100 men with a positive family history, demonstrated that screening biopsy is feasible and safe [4]. The main PROFILE cohort study aims to recruit 700 men, aged 40-69 years, either of Afro-Caribbean descent or with a positive family history.…”
mentioning
confidence: 99%